Allium karakocanense (Amaryllidaceae; Allium sect. Allium), a new species from eastern Anatolia (Türkiye) - Behçet Lütfi̇; Gülbasan İbrahi̇m Hali̇l (Phytotaxa, 2025)
Allium karakocanense, described here as a new species from Karakoçan District (Elazığ), is known from a single locality. In this study, the diagnostic characters of the new species are discussed and taxonomic evaluations are presented. Although the new species has some similarities with Allium ampeloprasum, A. pseudoampeloprasum, A. affine and A. bourgeaui, it differs significantly from these species in terms of its leaf and bracteole characteristics, as well as some features such as tepal color and stamen structure. Its bulb, leaf, inflorescence and flower structures were investigated using scanning scanner and images were taken from a binocular microscope for higher magnification. In addition to the ecological data, IUCN conservation status and distribution map of the new species, the distributions of related species are also given.